The post-Keynesian "crowding-in" policy meme: Government-led semi-autonomous demand growth - Brett Fiebiger (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
A recent literature has explored the role of semi-autonomous demand growth. This paper builds on the literature by incorporating a Lernerian government semi-autonomous demand function and an endogenous supply-side. Our main purpose is threefold. First, we wish to contribute to the case for crowding-in effects, especially in the long-run. Second, we confirm the Keynesian/Kaleckian pedigree of the capital stock adjustment principle. Third, we contrast core post-Keynesian ideas on demand-led supply-side endogeneity with the alternative neo-Marxian neo-Harrodian proposition of an exogenously-given natural growth rate, and find the latter lacking.
Keywords: B22; B50; E11; E20; E60; O42; 330; Fiscal policy; Crowding-in; Semi-autonomous demand; Capital stock adjustment principle